EVALUATION OF CHARACTER EDUCATION PROGRAM AT SDN TANJUNG DUREN UTARA 02 JAKARTA - ASTUTI, Ummi Widya (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2024)
This study evaluates the implementation and success of the character education program at SDN Tanjung Duren Utara 02 Jakarta using the CIPP model (Context, Input, Process, Product). The research aims to identify strengths and gaps in the program while providing recommendations for improvement. Participants include the principal, teachers, and parents, with data collected through interviews, observations, and documentation, then analyzed descriptively and qualitatively. The findings indicate that the program has met most evaluation criteria but requires improvement. In the context stage, the program’s vision, mission, and objectives have been effectively socialized, but the absence of a formal implementation team decree (SK) leads to varied understandings of roles and responsibilities. The input stage highlights a need for stronger principal supervision and improvements in facilities to support consistent program quality. In the process stage, teachers are encouraged to apply character values more consistently in both classroom and extracurricular activities. The product stage shows promising results in fostering character education among students, but limited monitoring and evaluation reduce the program's overall effectiveness in achieving its goals. Overall, the character education program is categorized as sufficient but requires further development. Recommendations include formalizing the program structure through an implementation team decree, increasing principal oversight, ensuring consistent application of character values, and conducting regular and systematic evaluations to optimize program outcomes.